Quantitative Determination of Potassium Sorbate in Muddy Flesh by Near-infrared Spectroscopy - Ni, Chao; Wang, Yuanhao; Zhao, Maocheng; Liu, Ying (Asian Journal of Chemistry, 2012)
In current study, near-infrared spectroscopy (NIRS) was used to measure the amount of potassium sorbate in muddy flesh (pork). Partial least squares (PLS) and principal component regressions (PCR) were used to establish quantitative models. The partial least squares model parameters were investigated using raw spectra and different processing methods, such as the multiplicative scatter correction and the first- and second-derivative and Savitzky-Golay smoothing techniques. Moreover, these parameters and the prediction results were discussed in detail. The coefficient of determination and root mean square error of cross-validation of the partial least squares regression were 0.964583 and 0.00106, respectively. These results demonstrate that near-infrared spectroscopy can be used to quantify potassium sorbate, which avoids the pollution of the gas and high-performance liquid chromatography columns.